Hubungan Beban Kerja Dan Burnout Terhadap Perilaku Caring Perawat Di RSU Hidayah Purwokerto - IASA, ARUM ANINDIKA; Susanti, Indri Heri; Wirakhmi, Ikit Netra (Jurnal Ilmiah Wahana Pendidikan, 2024)
Nurses are the main component in the hospital, working on standby within 24 hours, with all patient conditions. Nurses in carrying out their duties and profession are prone to physical and mental fatigue and are very vulnerable to burnout at work so that it will affect patient caring. This study aims to determine the relationship between workload and burnout to nurses caring at Hidayah RSU Purwokerto. This research method is descriptive quantitative, survey research method which is analytic in nature with a cross sectional approach. Population of 30 nurses and 203 patients. Sampling technique with purposive sampling technique on 135 patients and total sampling on 30 nurses. The research used the Maslach Burnout Inventory-Human Service Survey (MBI-HSS), the workload questionnaire from Nursalam (2016) and the caring behavior questionnaire from Nursalam (2015). The results of the study showed that the majority of nurse respondents aged between 25-34 years were 20 (66.7%). The workload of the nurses in the moderate category was 19 (63.3%), the burnout of the nurses in the moderate category was 17 (56.7%), and the caring behavior of the nurses in the moderate category was 74 (54.8%). Characteristics of the patients aged between 45-55 years were 62 (45.9%). The results of the Spearman rank test showed that there was a relationship between workload and caring behavior (p-value 0.018) with moderate relationship strength and there was a relationship between burnout and nurse caring behavior (p-value 0.009) with moderate relationship strength at Hidayah General Hospital Purwokerto.